Galileo's battle for the heavens [videorecording (DVD)] - Jones, Peter; Schrieber, Liev; Callow, Simon, 1949-; Nardi, Laura; Fraser, John, 1931-2020-; Jargo, Alexa; Sobel, Dava (WGBH Boston Video, 2006)
Dramatization of Galileo Galilei's life, including his scientific achievements and his defense of his controversial theory that the earth revolves around the sun. Also includes how letters from his illegitimate daughter, Maria Celeste, a cloistered nun, have shed new light on Galileo's discoveries and his trial for heresy.